Dança Circular Sagrada : um estudo sobre as representações corporais do Grupo Roda do Mato - Silva, Elisama Santos da (2016)
The main goal of this work is to identify the historic, sociocultural and practical elements involved the Sacred Circle Dance, from beings and reports from Roda do Mato group participants. In order to do so, it was necessary to investigate the memories related to dance, to report the feelings resulting from beings and, finally, to comprehend the logics behind the practice. As theoretical approach, it was made a bibliographical survey about the following axis: The Sacred Circular Dance and its configurations, observing aspects such as step by step, the sacred, the symbolism of the circle, among other relevant points to be considered. Such axes sustain the discussions in this study, in order to establish relationships between the literature and the reality found. The research is characterized as descriptive, showing a qualitative approach. Data were built with the participation of 8 dancers, being 5 women and 3 men, aged 19-65 years old. The data collecting instruments were photographic records and interviews with the group participants, record individually and in neutral environment. In general, for these dancers, the Sacred Circular Dances are understood as traditional folk dances from all around the world, which have as feature the possibility of approaching between people. Its steps are simple, full of symbolisms involving spirituality. Besides the mentioned ones, they help to improve physical, cognitive, emotional and spiritual aspects. It is important to regard that each dancer comprehends Sacred Circular Dance the way they need it, so each reason for entry and permanence, for example, is private. That is, the dance is understood as what we do of it or what it does from/by us.